The Demography Impact On Financial Literacy An Empirical Studies in Indonesia (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2022)
The primary purpose of the research is to explore the determinant of financial literacy from the demography perspective in Indonesia. The research will study the demography variable that determine the usage of financial products. The research will be focused on seven primary financial products. The research will be based on a survey of 320 respondents from all of Indonesia's main islands, such as Jawa, Sumatera, Sulawesi, Kalimantan, and Papua. In this research, we used a binary logit regression technique with SPSS Software to test the research model. The research is qualitative research method. The empirical results show that the primary determinant for a person to have a financial product, such as saving account, credit card, e-money, e-wallet, investment in stock, and insurance is their income level. Saving to income ratio is also a determinant for saving, credit card, e-money, and stock investment. Education level is a determinant for the usage of credit card, e-wallet, stock investment, and social insurance. Ownership of car and house is a determinant for credit card usage, e-money, e-wallet, and stock investment. Domicile is a determinant for the e-wallet and insurance usage. All variables are significant at a <10%.